PATHOLOGIES OF REPRODUCTIVE ORGANS OF CASPIAN FEMALE SEALS (PHOCA CASPICA, GMELIN, 1788) - V. V. Volodina; N. N. Fedorova; M. P. Grushko (Юг России: экология, развитие, 2016)
The aim is to compare morphofunctional conditions of the ovaries and uteruses of Caspian female seals born between the end of XX and beginning of XXI centuries.Methods. We have analyzed the reproductive organs of 16 female seals in the periods of October - November of 2011, 2012 and 2014. Biological material has been treated in accordance with conventional techniques in histology. Diagnosis and assessment of pathological changes in the bodies of seals have been carried out by classifications of L.A. Lesnikov and I.D. Chinareva.Results. We have identified early aging of gonads in sexually mature Caspian female seals due to the development of sclera-cystic ovary syndrome. Besides we have detected the necrosis of epithelial cells in the uterus as well as signs of uterine tissue edema. The myometrium has signs of quite significant bleeding. The nature and degree of morphological and functional disturbances detected in the reproductive organs of the Caspian female seals can be classified as chronic toxic damage.Conclusions. Earlier studies show the symptoms of endometriosis in the uterus of female pinnipeds born during the late XX century. These same individuals also suffered from sclera-cystic ovary syndrome. The pathological processes correspond to degrees II and III. The nature and extent of (III and IV degrees) morphological and functional disorders found in the ovaries and uterus of Caspian female seals born in XXI century indicate the identity of the pathologic features in the reproductive organs, but modern individuals have a higher degree of irreversible morphological and functional disorders indicating the degradation of the population P. caspica.